Differences in Learning Outcomes of Students' Two-Variable Linear Equation System in View of the Application of the Learning Model - Hamid, Abdul; Sulaiman, Mahfudz; Lusiyanto, Heru (Journal of Education and Learning Mathematics Research (JELMaR), 2024)
In the focus of the discussion of Linear Equation of Two Modes, this study intends to examine the differences in learning outcomes between students who follow learning with direct method (DI) and students who follow learning with problem-based method (PBL). This study used a semi-exploratory method involving MTs Nurur Rohmah students who were divided into control and experimental groups with 20 students each. The control group was taught with PBL model, while the experimental group was taught with DI model. Data were collected through a learning outcome test (posttest) given to students in both classes. Both groups had non-normally distributed data when tested for normality of posttest data. Mann-Whitney test showed that the learning achievement. The ability to solve the Two-Variable Linear Equation System of students who learned with the Problem-Based Learning method was overall better than students who learned with the direct learning method.